2012
DOI: 10.1128/jb.00881-12
|View full text |Cite
|
Sign up to set email alerts
|

Function and Regulation of Isoforms of Carbon Monoxide Dehydrogenase/Acetyl Coenzyme A Synthase in Methanosarcina acetivorans

Abstract: Conversion of acetate to methane (aceticlastic methanogenesis) is an ecologically important process carried out exclusively by methanogenic archaea. An important enzyme for this process as well as for methanogenic growth on carbon monoxide is the five-subunit archaeal CO dehydrogenase/acetyl coenzyme A (CoA) synthase multienzyme complex (CODH/ACS) catalyzing both CO oxidation/CO 2 reduction and cleavage/synthesis of acetyl-CoA. Methanosarcina acetivorans C2A contains two very similar copies of a six-gene opero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 45 publications
1
33
0
Order By: Relevance
“…This complex cleaves acetyl-CoA into a methyl group, an enzyme-bound carbonyl, and free CoA. The methyl group is transferred by CODH/ACS to the C 1 -transferring cofactor tetrahydrosarcinapterin and subsequently reduced to methane (Matschiavelli et al, 2012). Concomitantly, methanosarcinal transcripts encoding methanogenesis were significantly enriched under salt stress.…”
Section: Resultsmentioning
confidence: 99%
“…This complex cleaves acetyl-CoA into a methyl group, an enzyme-bound carbonyl, and free CoA. The methyl group is transferred by CODH/ACS to the C 1 -transferring cofactor tetrahydrosarcinapterin and subsequently reduced to methane (Matschiavelli et al, 2012). Concomitantly, methanosarcinal transcripts encoding methanogenesis were significantly enriched under salt stress.…”
Section: Resultsmentioning
confidence: 99%
“…In this respect, it is of interest that the genome of Methanosarcina acetivorans harbors one gene for CO dehydrogenase in a cluster with a gene for acetyl-CoA synthase and an orphan gene for CO dehydrogenases, either one of which can be disrupted without affecting growth of the methanogen on CO, methanol, or acetate, indicating that each of the two CO dehydrogenases can function in vivo in both directions (60,61).…”
Section: Ferredoxin-dependent Transhydrogenase (Nfnmentioning
confidence: 99%
“…S6), a similar regulation can be expected in other Methanosarcina species. Similarly, for Methanosarcina acetivorans containing two operons encoding ACDS it has been shown that substrate dependent regulation occurs beyond transcriptional regulation (Matschiavelli et al ., ), which is most likely due to early elongation termination (see above). We assume that the presence of a sRNA 41 homologue in M. acetivorans , also known to fix molecular nitrogen, plays a similar role in nitrogen dependent post‐transcriptional regulation by the sRNA 41 homologue on M. mazei .…”
Section: Discussionmentioning
confidence: 99%
“…5, Supporting Information Fig. S5A), is known to be transcriptionally regulated in response to substrate availability (i.e., acetate) (Hovey et al, 2005;Anderson et al, 2009;Matschiavelli et al, 2012). Since M. mazei G€ o1 3A requires long adaptation times for growth on acetate, as sole energy and carbon source, methylotrophic growth on methanol under acetate depletion was chosen to evaluate acetate dependent regulation.…”
Section: Srna 41 Target Identificationmentioning
confidence: 99%